COMPREHENSIVE ECOHYDROLOGY STUDY TO SUPPORT AGRICULTURE AND WATER RESOURCES MANAGEMENT IN PEATLAND AREA-CENTRAL KALIMANTAN - Sutapa, Ignasius Dwi Atmana; Maftuah, Eni; Sunaryani, Astried; Pawitan, Hidayat (LIPI Press, 2017)
Peat swamp forest is a unique and fragile ecosystem, with specific flora and fauna that play important roles in maintaining healthy natural conditions with high economic values. This habitat also has important role for equilibrium and maintenance of living environment such as water reservoir, carbon storage, climate change, and biodiversity. Utilization of peatland for agriculture, plantations, and other activities often lead not only to controversy, but also cause land and ecosystem degradation, including water resources availability. The objective of this research was to study comprehensive ecohydrology aspects in ex-mega rice project in Central Kalimantan in order to support sustainable agricultural practices and water resources management in peatland areas. The results of the study showed that the sustainability of agricultural systems in peatland was strongly influenced by ecological aspect. This aspect can be carried out from the condition of water management system, water color condition, and possible incidence of fires. The level of suitability for crops plantation was low (S3), with the limiting factors of pH, nutrient availability, and the risk of inundation. In this case, water gates should be installed to improve water management system. Water quality in this area was typical of peat water and do not meet the requirement for daily use for the local people.